IMPLEMENTASI METODE SAW DAN WASPAS DENGAN PEMBOBOTAN ROC DALAM SELEKSI PENERIMAAN PESERTA DIDIK BARU (Studi Kasus: Madrasah Tsanawiyah (MTs) Negeri Kisaran Kabupaten Asahan Provinsi Sumatera Utara Tahun Ajaran 2018/2019) - Nabila, Eva Salsa; Rahmawati, Rita; Widiharih, Tatik (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2019)
Multi Attribute Decision Making (MADM) is one of the decision-making methods to determine the best alternative from a number of alternatives based on certain criteria. There are several methods that can be used to solve MADM problems including Simple Additive Weighting (SAW) and Weighted Aggregated Sum Product Assesmen (WASPAS). Both methods are applied in the selection of prospective new students. In this study, MTsN Kisaran selected 192 students received from 422 registrans and determined certain criteria to get quality students. The criteria determined are the value of the national exam, the value of the Al-Qur'an test, and the value of the academic potential test. The method applied is SAW and WASPAS with the weighting Rank Order Centroid (ROC). Then a sensitivity analysis is carried out to determine a viable methods selected to obtain optimal results. This research was designed with the help of the Matlab GUI as a computing tool to simplify and accelerate the selection process. Based on the results of the study, the average percentage value of sensitivity for the SAW method was -0.82% while the WASPAS method was -0.87%. With the existence of sensitivity analysis it can be known the most appropriate method for this case is the SAW method. Keywords: Students, SAW, WASPAS, ROC, Sensitivity, GUI Matlab.